2013
DOI: 10.1088/1009-0630/15/6/13
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Methane to C2Hydrocarbons and Hydrogen Using a Gliding Arc Reactor

Abstract: Methane conversion has been studied using gliding arc plasma in the presence of argon. The process was conducted at atmospheric pressure and ambient temperature. The focus of this research was to develop a process of converting methane to C2 hydrocarbons and hydrogen. The main parameters, including the CH4/Ar mole ratio, the CH4 flow rate, the input voltage, and the minimum electrode gap, were varied to investigate their effects on methane conversion rate, product distribution, energy consumption, carbon depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
(35 reference statements)
0
25
0
Order By: Relevance
“…Non-oxidative CH 4 coupling has been performed in multiple systems, gliding arc being one of them. 87,88 In ref. 88, approximately 40% CH 4 conversion was achieved with 20% selectivity towards C 2 H 2 and 40% towards H 2 , which were the main products besides pure carbon and power was found to have little effect on the product distribution.…”
Section: Non-oxidative Ch 4 Conversionmentioning
confidence: 99%
“…Non-oxidative CH 4 coupling has been performed in multiple systems, gliding arc being one of them. 87,88 In ref. 88, approximately 40% CH 4 conversion was achieved with 20% selectivity towards C 2 H 2 and 40% towards H 2 , which were the main products besides pure carbon and power was found to have little effect on the product distribution.…”
Section: Non-oxidative Ch 4 Conversionmentioning
confidence: 99%
“…Hu et al[98] performed CH4 reforming in the presence of Ar in a GA. CH4/Ar ratio, CH4 flow rate, input voltage and minimum electrode gap were varied to investigate their effects on CH4 conversion and product distribution. As Ar content increased, CH4 conversion as well as C2 and H2 selectivity increased because the Ar metastable state enhanced electron impact reactions.…”
mentioning
confidence: 99%
“…In general, the gas-phase non-equilibrium plasma technology includes dielectric barrier discharge (DBD), corona discharges, microwave (MW) discharge and gliding arc discharge (GAD). This promising technology has advantages of high energy density, mild reaction conditions, small-scale equipment, as well as the rapid response time, and has already been applied in many fields like material fabrication and surface treatment, [7][8][9] the decomposition of volatile organic compounds (VOCs), [10,11] direct conversion of simple hydrocarbons to high-value chemicals [12,13] as well as hydrocarbon fuel reforming. [14,15] It is also reported that the assistance of plasma can improve the performance of catalysts.…”
Section: Introductionmentioning
confidence: 99%